Validitas Lembar Kerja Berbasis Masalah Untuk Meningkatkan Kemapuan Literasi Sains Pada Materi Pemanasan Global (Universitas Negeri Surabaya, 2023)
Scientific literacy is the ability which must be owned by the students to analyze and apply the concept of physics in solving daily life problem. This study aims to determine and analyze the validity of problem-based worksheets to improve scientific literacy skills in the developed global warming material. The method used is the Research & Development (R&D) method with the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). In this study, three stages were used, namely the analysis stage, the design stage, and the development stage. At the analysis stage (analyze) by determining the worksheets that students need. At the design stage, the worksheet design is developed. At the development stage it was carried out by compiling and conducting validation which was carried out by 3 validators consisting of 2 expert lecturers and 1 high school teacher. The validity of the worksheet is assessed on the content and construction aspects. The advantages of the developed worksheet are using a problem-based learning model which contains real problems in everyday life and exercises indicators of scientific literacy. The drawback is that worksheets cannot be accessed digitally and two stages of implementation and evaluation have not been carried out. Based on both content and construction aspects, the total average of the three validators was 88.06%. The results of the validation show that the worksheet used is declared valid and can be used in the learning process to improve students' literacy skills and can be used as a solution in learning physics to improve scientific literacy skills. That way, the benefits of the research are the usefulness of the results of the research later, both for the benefit of developing worksheets and for the benefit of science. Keywords: Worksheets, Validity, Problem Based, Science Literacy